Tinjauan Upacara Adat Perkawinan dan Tata Rias Pengantin Solo Putri di Kecamatan Luhak Nan Duo Kabupaten Pasaman Barat - Janah, Miftakul; Yanita, Merita (Lembaga Yasin AlSys, 2025)
Although traditional Javanese wedding ceremonies and the Solo Putri bridal makeup style continue to be preserved by the Javanese community in Luhak Nan Duo District, West Pasaman Regency, modernization, socio-economic changes, and declining youth understanding of traditional values have led to the simplification and alteration of customary practices. This study aims to describe the sequence of traditional Javanese wedding ceremonies, analyze the makeup, hair arrangement, and bridal attire of the Solo Putri style, along with their underlying philosophical meanings. A descriptive qualitative approach was employed, with data collected through field observation, in-depth interviews, and documentation involving community leaders, cultural elders, and bridal makeup artists. Data analysis was conducted through stages of reduction, presentation, and conclusion drawing, by comparing current practices with traditional standards. The findings indicate that most core ceremonies—such as the engagement, wedding contract (akad nikah), and panggih ceremony—are still preserved in accordance with tradition, while other rituals like siraman, midodareni, and ngunduh mantu are increasingly being abandoned. The Solo Putri makeup style has undergone modifications in materials for paes, cosmetic color choices, and the use of ready-made hair buns instead of traditional pandan buns. Bridal attire has also adapted to modern trends, although it retains distinctive elements such as velvet kebaya and batik cloth featuring the sidoasih motif. These findings underscore the importance of preserving traditions through adaptive practices that respect cultural values, and highlight the need to educate younger generations to ensure the continuity of cultural heritage amidst changing times.